The Wild West : an interactive history adventure - Lassieur, Allison (You choose books, 2009)
"Describes the people and events of the age of the Wild West in the year 1876. The reader's choices reveal the historical details from the perspective of an outlaw, a lawman, and a fortune-seeker in Deadwood, Dakota Territory"--Provided by publisher.